Anthocyanins Potentially Contribute to Defense against Alzheimer’s Disease - Afzal, Mohammad (Molecules, 2019)
Anthocyanins (ANTs) are plant pigments that belong to a flavanol class of polyphenols and have diverse pharmacological properties. These compounds are primarily found in fruits and vegetables, with an average daily intake of 180 mgd(−1) of these compounds in the developed world. ANTs are potent antioxidants that might regulate the free radical-mediated generation of amyloid peptides (Abeta-amyloids) in the brain, which causes Alzheimer’s disease (AD). This study presents a literature review of ANTs from different berries and their potential therapeutic value, with particular emphasis on neurodegenerative AD, which owing to oxidative stress. This review also highlights reactive oxygen species (ROS) generation through energy metabolism, nitrogen reactive species, the role of transition metals in generating ROS, and the radical-quenching mechanisms of natural antioxidants, including ANTs. The current status of the bioavailability, solubility, and structure activity relationship of ANTs is discussed herein.